Balance of payments manual - International Monetary Fund. (Washington : International Monetary Fund, 1977)
This book had been issued by IMF to guide member countries in making their regular reports on the balance of payments, as stipulated in the Fund's Articles of Agreement.
Includes index.
Includes bibliographic footnotes
usc 30/04/18
Loans
Keywords: Balance of payments; International finance; Balance of trade